Survival models of recidivism among juvenile delinquents - Gruenewald, Paul J. (Journal of quantitative criminology, 1989)
Among juveniles, the probability of recidivism has a curvilinear relationship to age. Rates of reoffending do not simply increase or decrease with age, but rather, they increase as a function of age up to a certain point of peak activity and decrease with increasing age thereafter. Because of this, the forms of recidivism functions between cohorts of widely varying ages will differ considerably. This renders inapplicable one model for the analysis of recidivism rates which assumes proportional hazards (Cox proportional hazards regression models). Appropriate models will posit curved nonmonotonic hazard functions. This paper compares fits of the exponential, Weibull, and log-normal models to recidivism data collected on samples of chronic juvenile offenders and finds generally closer estimation of the recidivism functions using the latter model. Implications for the development of models of recidivism are discussed.